Папиллярный рак щитовидной железы в Украине в период после аварии на Чернобыльской АЭС - Tronko, M.D.; Komisarenko, I.V.; Kovalenko, A.Ye.; Omelchuk, O.V. (Ендокринологія | Endokrynologia, 2020)
Папиллярный рак щитовидной железы в Украине в период после аварии на Чернобыльской АЭС